A GDP impact evaluation of R&D investments in Romania using the CGE model Rhomolo - O. Diukanova; M. Chioncel (European Commission, Joint Research Centre (JRC), 2021)
This study evaluates the potential economic impacts of Research & Development (R&D) investments in Romania during the 2021-2027 policy cycle. The assessment is based on three distinct R&D investments scenarios: (1) 2% Gross domestic Expenditure on R&D (GERD) intensity target achieved by 2029, with equal split between public and private investment, in accordance with the R&D investment targets declared in the national strategic documents; (2) gradual increase of GERD intensity to 2.25% by 2029, with public investment of 1.25% of GDP (in line with the new ERA target); and (3) 0.48% of GDP, "business as usual' scenario (following the same investment pattern as in the past years). The results of computer simulations with the RHOMOLO model, which is a dynamic multi-regional computable general equilibrium (CGE) model developed by the Joint Research Centre (JRC) of the European Commission, show that the most pronounced GDP impacts in Romania would be achieved with the highest intensity of R&D policy funding. Aside from the capital city region RO32, the less developed regions RO12, RO22, RO31 and RO41 exhibit the highest GDP multipliers across Romanian regions, which indicates the high potential of R&D funding in these regions. The strongest spillover effects emerge from the regions that in certain years make substantial R&D domestic private and public investments relative to the size of their economies. Although R&D investments augment factor productivity that depreciates gradually in the absence of continuous funding, the strength of lagged effects of R&D funding depends on the intensity of R&D investments rather than on the source of funding. However, in the short run, the economic cost for Romania is determined by the source of R&D investments: despite their small size, the EU investments that are largely financed by other EU member states, produce quite sizeable GDP multipliers in Romania compared to the national public and private investments.
Keywords: 330; RHOMOLO; Cohesion Policy; regional growth; regional development; Romania